2015
DOI: 10.1158/1055-9965.epi-14-1415
|View full text |Cite
|
Sign up to set email alerts
|

De NovoPost-Diagnosis Aspirin Use and Mortality in Women with Stage I–III Breast Cancer

Abstract: Background: Aspirin use has been associated with significant reductions in breast cancer-related mortality in some observational studies. However, these studies included women who initiated aspirin use before breast cancer diagnosis. It is unclear whether initiating aspirin use after diagnosis is associated with similar reductions in mortality. This study investigates associations between de novo post-diagnostic aspirin use and all cause, breast cancer-specific mortality.Methods: Women, ages 50 to 80, with a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
(46 reference statements)
1
27
1
Order By: Relevance
“…The potential anti-cancer effect of aspirin has been hypothesised to be, in part, mediated through suppression of oestrogen biosynthesis [35,36], but similar to our study, two previous cohort studies found no difference in associations by hormone receptor status [10,17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The potential anti-cancer effect of aspirin has been hypothesised to be, in part, mediated through suppression of oestrogen biosynthesis [35,36], but similar to our study, two previous cohort studies found no difference in associations by hormone receptor status [10,17].…”
Section: Discussionsupporting
confidence: 88%
“…In our analysis, we lagged medication use after diagnosis by 6 months and this period was varied in sensitivity analysis. Other epidemiological studies have reported no association for aspirin use after diagnosis and risk of breast cancer death [15,16,17]. Similar to our investigation, these studies assessed the impact of low-dose aspirin specifically and drug use was captured using population-based prescribing databases.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…23 Post-diagnostic aspirin use (both low-dose and high-dose) has been associated with a 50% reduction in breast cancer recurrence/mortality in some, 18,28 but not all studies. 19,2125 Research on the effect of NSAIDs on breast cancer recurrence or mortality also report conflicting findings. 2022,29,30 Decreased recurrence has been correlated with perioperative use of ketorolac 29,30 and use of any NSAID.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a relatively recent study addressed the same problem and using sophisticated methods including laser capture microdissection and next generation sequencing in breast tumor tissues versus peripheral blood DNA, it was confirmed that higher CAG repeat variants associate with risk of BC [48]. Recent studies also showed that aspirin may reduce [71] or have no influence [72] on BC-related mortality. As mentioned, the inconsistent results of epidemiological studies may relate to heterogeneous nature of investigated patient populations.…”
Section: Discussionmentioning
confidence: 93%